A Partial Charred Wooden Bowl From Aztalan (47JE1), Wisconsin. Issue 3 (1st September 2020) - Hawley, Marlin F.; Schroeder, Sissel; Widga, Christopher C.
ABSTRACT: Fragments of a charred wooden bowl were recovered from Aztalan during excavations by the State Historical Society of Wisconsin (SHSW) in 1964. Recent advances in analytical methods facilitated a multidimensional study of these fragments. Radiocarbon-dated to cal AD 994–1154 and found in association with Late Woodland, Mississippian, and hybrid forms of ceramics, the bowl augments our understanding of perishable technologies in these cultural contexts. 3-D models of the fragments allow for a virtual reconstruction of a portion of the bowl, which was carved from a solid piece of ash. Strontium isotope analysis of the wood indicates that the bowl was manufactured from wood locally available to the people at Aztalan.